Electron beam induced changes in optical properties of glassy As35S65 chalcogenide thin films studied by imaging ellipsometry - Janíček, Petr; Funke, S.; Thiesen, P. H.; Šlang, Stanislav; Pálka, Karel; Mistrík, Jan; Grinco, Marina; Vlček, Miroslav (Elsevier Science BV, 2018)
Spectroscopic imaging ellipsometry was used to study 50 mu m x 50 mu m squares recorded into glassy As35S65 thin film by electron beam with different exposure doses. Optical constants (refractive index n and extinction coefficient k) of electron exposed areas were determined from imaging ellipsometric data recorded over a spectral range 390-800 nm. Complex dielectric permittivity of each of electron exposed square (glassy As35S65 with different electron exposure dose) was parametrized by a Tauc-Lorentz oscillator. Gradient optical model with the refractive index changing linearly within the layer thickness was used. Evaluation of parameters of Tauc-Lorentz oscillator revealed decrease of energy bandgap, increase of the refractive index in whole recorded spectra (more pronounced at the top of the film) and increase of extinction coefficient in the part of spectra where the material absorbs with the increasing electron exposure dose used for exposure of the squares. The decrease in local disorder with increasing electron exposure dose is quantified from the short wavelength absorption edge onset using a Mott-Davis model. The dependence of the parameters of Wemple-DiDomenico model for the transparent part of the optical constants spectra on electron exposure dose is shown. Thin film with recorded image was subsequently etched in amine based solution in aprotic solvent. While native film was fully etched off the remaining height of the exposed areas is increasing with the increasing electron exposure dose used. Knowledge of the changes of optical properties and etching rates induced by electron beam of different exposure doses can be used for fabricating of optical elements by high resolution electron beam lithography.
Změny v optických vlastnostech tenkých vrstev chalkogenidového skla As35S65 indukované elektronovým paprskem studované zobrazovací elipsometrií
Keywords: Imaging ellipsometry; Optical properties; Chalcogenide glass; Thin films; Micro-structuring; Zobrazovací elipsometrie; Optické vlastnosti; chalkogenidové sklo; Tenké filmy; Mikro-strukturování